2016
DOI: 10.1523/jneurosci.3753-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Cue Reliability Represented in the Shape of Tuning Curves in the Owl's Sound Localization System

Abstract: Optimal use of sensory information requires that the brain estimates the reliability of sensory cues, but the neural correlate of cue reliability relevant for behavior is not well defined. Here, we addressed this issue by examining how the reliability of spatial cue influences neuronal responses and behavior in the owl's auditory system. We show that the firing rate and spatial selectivity changed with cue reliability due to the mechanisms generating the tuning to the sound localization cue. We found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 57 publications
(11 reference statements)
9
56
0
Order By: Relevance
“…For cue reliability to influence behavior, a decrease in reliability must cause an increase in tuning widths for that cue. It has been shown that changing the reliability of IPD causes IPD tuning curves to widen, consistent with the widening of the likelihood function as reliability changes (Cazettes et al, 2016). This is distinct from a reweighting of inputs in linear neural responses that is predicted by the PPC model (Fetsch et al, 2011).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…For cue reliability to influence behavior, a decrease in reliability must cause an increase in tuning widths for that cue. It has been shown that changing the reliability of IPD causes IPD tuning curves to widen, consistent with the widening of the likelihood function as reliability changes (Cazettes et al, 2016). This is distinct from a reweighting of inputs in linear neural responses that is predicted by the PPC model (Fetsch et al, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…While this is suboptimal, it simplifies the probability distribution that the brain must learn while representing the statistical relationship between the environment and the cues, which is the central component of the perceptual inference problem. Furthermore, for large populations, inferences made using the low-dimensional distribution ( p X|C 1 , C 2 ( X |C 1 , C 2 ) may closely approximate inferences made using the high-dimensional distribution ( p X| r 1 , r 2 ( X | r 1 , r 2 ) (Cazettes et al, 2016). …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous reports have investigated the selectivity of midbrain neurons to the variability of spatial cues in the owl's auditory system (Cazettes et al 2014;Fischer and Peña 2017). These studies provided evidence of how sensory reliability could be represented (Fischer and Peña 2011;Rich et al 2015;Cazettes et al 2016) and integrated into an adaptive behavioral command (Cazettes et al 2018). Although the ITD statistics relevant to owls and humans differ based on the frequency range over which ITD is detected, and the coding of ITD cannot be assumed identical across species (Schnupp and Carr 2009), results of the present study support the hypothesis that specific ITD statistics, ITDrc and ITDv, determine human sound localization discriminability and novelty detection of acoustic spatial deviants.…”
Section: Discussionmentioning
confidence: 99%
“…Observations of the owl's brain and behavior suggest that the answer is 'very much'. For example, the sound localization system of the barn owl implements various mathematical operations, such as multiplication (Pena and Konishi, 2001), averaging (Christianson and Peña, 2006), crosscorrelation (Saberi et al, 1998;Fischer et al, 2008) and Bayesian inference (Cazettes et al, 2016;Fischer and Peña, 2011). These operations had been predicted by models of human psychophysics (Jeffress et al, 1962;Licklider, 1959;Sayers and Cherry, 1957;Stern and Steven Colburn, 1978;Stern et al, 1988), but never demonstrated in neural responses.…”
mentioning
confidence: 99%